Protective immunity in murine histoplasmosis: functional comparison of adoptively transferred T-cell clones and splenic T cells. - Deepe, G S (1988)
In this study, I examined whether a murine T-cell line and three clones that recognize Histoplasma capsulatum antigens in vitro could confer protection in vivo against a challenge of Histoplasma yeasts. C57BL/6 mice were each inoculated with 5 X 10(4) yeasts intravenously; 1 h later, 5 X 10(6) or 2 X 10(7) resting T cells were inoculated intravenously. At week 1 of infection, the T-cell line and all clones failed to reduce the number of H. capsulatum CFU in the spleens of mice compared with numbers in infected controls. Administration of recombinant interleukin 2 or cyclophosphamide to infected mice did not potentiate the functional activity in vivo of either the T-cell line or the clones. In contrast, inoculation with 2 X 10(7) CD4+ but not CD8+ cells isolated from the spleens of mice immunized with 10(6) viable yeast cells sharply diminished the number of CFU in the spleens of infected animals. Moreover, splenic CD4+ cells from immune mice transferred a delayed-type hypersensitivity response, whereas the T-cell line and clones did not. Injection Injection of an equal number of cloned T cells and CD8+ splenocytes from immune mice did not transfer resistance to infected mice. Additional studies were undertaken to determine if the ineffectiveness of cloned T cells was associated with a failure to migrate to and survive within spleens of infected mice. B6.PL Thy-1a/Cy mice, which are genetically identical to C57BL/6 mice except that T cells of the former bear Thy-1.1 rather than Thy-1.2, were inoculated with Histoplasma yeasts and then injected with immune CD4+ splenocytes or a T-cell clone. At days 1 and 7 of infection, virtually no Thy-1.2+ cells were detected in the spleens of infected mice given cloned T cells. However, the spleens of animals inoculated with immune CD4+ cells contained a small but significant (P less than 0.01) proportion of Thy-1.2+ cells at both day 1 and day 7 postinoculation of H. capsulatum. Thus, the failure of T-cell clones to transfer protection against H. capsulatum may be explained by defective trafficking or poor survival in vivo or both.